2022
DOI: 10.1158/1538-7445.am2022-3495
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3495: A novel Mediterranean dietary intervention for prostate cancer

Abstract: Active surveillance (AS) is a safe management strategy for men with low-risk prostate cancer; however, nearly 35% of men on AS will undergo definitive treatment within 4 years, most commonly due to disease progression. Determining a non-invasive means of limiting disease progression would allow men to avoid quality of life issues associated with radical prostate treatment. Some modifiable factors, such as obesity and lipid levels, are associated with prostate cancer risk, though no behavioral intervention has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regard to prostate cancer, although following the Mediterranean diet may reduce its incidence, the curative aspect has not been well delineated [44] . It is reported that the antioxidant and hypolipidemic action may be of benefit to individuals with localized prostate cancer [45] . However, it is well established that a Western diet rich in processed foods and high in calories, may be one of the causes of the increase in this disease.…”
Section: Mediterranean Diet: Prevention and Treatment Of Major Chroni...mentioning
confidence: 99%
“…With regard to prostate cancer, although following the Mediterranean diet may reduce its incidence, the curative aspect has not been well delineated [44] . It is reported that the antioxidant and hypolipidemic action may be of benefit to individuals with localized prostate cancer [45] . However, it is well established that a Western diet rich in processed foods and high in calories, may be one of the causes of the increase in this disease.…”
Section: Mediterranean Diet: Prevention and Treatment Of Major Chroni...mentioning
confidence: 99%